2015
DOI: 10.1039/c4md00478g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of a series of resveratrol analogues as potent anti-cancer agents that target tubulin

Abstract: A series of novel diarylacrylonitrile and trans-stilbene analogues of resveratrol has been synthesized and evaluated for their anticancer activities against a panel of 60 human cancer cell lines. The diarylacrylonitrile analogues 3b and 4a exhibited the most potent anticancer activity of all the analogues synthesized in this study, with GI50 values of < 10 nM against almost all the cell lines in the human cancer cell panel. Compounds 3b and 4a were also screened against the acute myeloid leukemia (AML) cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…It can be seen from our results that ISO and Rsv have high structural similarities with combretastatin, a colchicine analog known to interact with the colchicine-binding site in tubulin [63,64]. Rsv is well known to interact with tubulin, and therefore ISO may also do so by maintaining its structural similarity with Rsv [26,57,65]. The docking results reconfirmed that ISO and Rsv bind to the colchicine binding site in the same orientation as combretastatin, and with a similar docking score.…”
Section: Discussionsupporting
confidence: 67%
“…It can be seen from our results that ISO and Rsv have high structural similarities with combretastatin, a colchicine analog known to interact with the colchicine-binding site in tubulin [63,64]. Rsv is well known to interact with tubulin, and therefore ISO may also do so by maintaining its structural similarity with Rsv [26,57,65]. The docking results reconfirmed that ISO and Rsv bind to the colchicine binding site in the same orientation as combretastatin, and with a similar docking score.…”
Section: Discussionsupporting
confidence: 67%
“…The most potent compound 6 (Figure ) with GI 50 values of <10 n m against almost all the cell lines in the human cancer cell panel, was also screened against the acute myeloid leukemia cell line, MV4‐1. Its Z analogue 7 is more potent than 6 at inhibiting tubulin polymerization in MV4‐11 cells; this fact was confirmed by molecular docking studies that indicated a common binding site for 6 and 7 on the α,β‐tubulin heterodimer, with a slightly more favorable binding for 7 relative to 6 , which is consistent with the results from microtubule depolymerization assays …”
Section: Synthetic Anticancer Stilbenessupporting
confidence: 76%
“…Its Z analogue 7 is more potent than 6 at inhibiting tubulin polymerization in MV4-11 cells;t his fact was confirmed by molecular docking studies that indicated ac ommon binding site for 6 and 7 on the a,btubulin heterodimer,w ith as lightly more favorable binding for 7 relative to 6,w hich is consistentw ith the resultsf rom microtubule depolymerization assays. [78] Compound 8 in Figure 4, was largely studied for its apoptotic activity in HL60 myeloblastica cute leukemia cell line inducing ap artial block of cells in Sp hase. [27] Subsequently,c ompound 8 was checked in an in vivo study in immunodeficient mice with HT-29 xenograft.…”
Section: Polymethoxy Stilbenesmentioning
confidence: 99%
“…Growth inhibitory or cytotoxic effects were measured by percentage growth (PG), which is proportional to optical density (OD) [23, 24]. OD measurements of SRB-derived color prior to and 48 hrs after exposure of cells to the test compound or vehicle control were recorded.…”
Section: Resultsmentioning
confidence: 99%